1998
DOI: 10.1002/(sici)1521-4141(199807)28:07<2234::aid-immu2234>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB in Th2 cells : delayed and long-lasting induction through the TCR complex

Abstract: Nucelar NF O B was analyzed in murine Th2 cells after stimulation via the TCR pathway. Signals delivered through the TCR/CD3 complex induced active NF O B translocation to the nucleus of Th2 cells after a late phase (24 h) of the activation process, which is in contrast to the rapid appearance of nuclear NF O B (3 h) in Th1 cells after the same stimulation. The slow kinetic of NF O B nuclear uptake in Th2 cells was not accelerated by CD28 triggering or under stimulation with antigen plus antigen-presenting cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Furthermore and in agreement with other studies, 38 stimulation of B-CLL cells with anti-CD40 induced high levels of NF-kB activity. To confirm the specificity of the NF-kB signal, a cold oligonucleotide competition assay with 50-fold molar excess of an unlabeled and unrelated competitor 39 was used (Figure 6b). Supershift assay showed that NF-kB complexes translocated predominantly p50-p65 heterodimers to the nuclear extracts (Figure 6c), as previously reported in normal and B-CLL cells.…”
Section: Pi3k/akt Activity Results In Activation Of Nf-kb In B-cll Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore and in agreement with other studies, 38 stimulation of B-CLL cells with anti-CD40 induced high levels of NF-kB activity. To confirm the specificity of the NF-kB signal, a cold oligonucleotide competition assay with 50-fold molar excess of an unlabeled and unrelated competitor 39 was used (Figure 6b). Supershift assay showed that NF-kB complexes translocated predominantly p50-p65 heterodimers to the nuclear extracts (Figure 6c), as previously reported in normal and B-CLL cells.…”
Section: Pi3k/akt Activity Results In Activation Of Nf-kb In B-cll Cellsmentioning
confidence: 99%
“…39 Nuclear proteins (2 mg) were incubated for 10 min in a final volume of 10 ml with 200 ng poly(dIdC) (Amersham Biosciences) before addition of 0.4 ng of 5 0 -end labelled ds-oligonucleotide kB, which contains an NF-kB binding site (5 0 CAA CGG CAG GGG AAT CTC CCT CTC CTT 3 0 ). 40 Binding reactions were allowed during 30 min at room temperature and electrophoresed in a 5% polyacrylamide gel in TBE (0.5 Â ).…”
Section: Electrophoretic Mobility Shift Assay (Emsa)mentioning
confidence: 99%
“…Taken together, these results suggest that IL-18 exerts its action on IL-4 production by NKT lymphocytes by amplifying the signaling pathway initiated by TCR/CD3 cross-linking. This might eventually occur through activation of NF-B, a NF that has been implicated in the transcription of IL-4 (36) and whose activation in response to IL-18 and TCR cross-linking has been reported (23,37). Alternatively, increased IL-4 production might also be promoted by the nuclear AP-1, whose activation by IL-18 has been suggested (38) and whose binding to the IL-4 promoter, possibly in combination with other NFs, triggers IL-4 transcription (39).…”
Section: Il-18 Enhances Il-4 Production By Nkt Lymphocytes At a Singlmentioning
confidence: 99%
“…Studies have shown that T-cell receptor engagement of Th1 T-helper cells leads to rapid activation of a p50:p65 heterodimer, whereas similar stimulation of Th2 cells leads to delayed activation of p65 complexes devoid of the p50 subunit, thereby possibly contributing to differential cytokine gene regulation (31). A more recent study has shown that differential induction of cRel-containing NF-nB complexes regulates cytokine-mediated priming of naive T cells to overcome their intrinsic refractoriness for cytokine production in response to T-cell receptor engagement (32).…”
Section: Introductionmentioning
confidence: 99%